Managing the transition from concussion to return to learn in postsecondary education: strategies based on principles of UDL - Gail Frost; Maureen Connolly (Collected Essays on Learning and Teaching, 2018)
Concussion is a functional brain injury that can produce physical, cognitive, emotional and sleep-related symptoms.  With correct management, most symptoms will resolve within a month and a gradual, progressive return to activity (cognitive and physical) that allows students to stay below the thresholds that make symptoms worse, can be started after the immediate post-impact rest period of 24-48 hours. The 6-step Return-to-Learn protocol works well to manage the return to the classroom for elementary and high school-aged students, however it is difficult to implement in a postsecondary setting, as it requires a level of monitoring not generally available through college or university student wellness centres. As a result, course instructors are often given the task of providing accommodations to help students recovering from concussion manage and master the content and complete the required work to pass their course. This paper will discuss the challenges facing the postsecondary student recovering from concussion and provide accommodation ideas and examples, with resources, that instructors may find helpful.